2022
DOI: 10.1007/s10741-021-10212-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimal effectiveness of heart failure management — an umbrella review of meta-analyses examining the effectiveness of interventions to reduce (re)hospitalizations in heart failure

Abstract: Heart failure (HF) is a major health concern, which accounts for 1–2% of all hospital admissions. Nevertheless, there remains a knowledge gap concerning which interventions contribute to effective prevention of HF (re)hospitalization. Therefore, this umbrella review aims to systematically review meta-analyses that examined the effectiveness of interventions in reducing HF-related (re)hospitalization in HFrEF patients. An electronic literature search was performed in PubMed, Web of Science, PsycInfo, Cochrane R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 291 publications
1
13
0
Order By: Relevance
“…The meta-analysis by Zhu et al [ 21 ] presented consistent results, reporting the beneficial effects of telemedicine strategies on all-cause hospitalisation, cardiac hospitalisation, all-cause mortality, and cardiac mortality. The positive effect of telemonitoring was also confirmed by Hafkamp et al [ 22 ], who found a lower risk of HF-related hospitalisations (HR = 0.86, 95% CI: 0.81–0.92, p < 0.001). Drews et al [ 5 ] summarised only studies in patients with HF decompensation within the previous month with intervention based on using telemonitoring, defined as the regular transmission of at least one physical variable at least once weekly.…”
Section: Telecare and Remote Disease Managementsupporting
confidence: 65%
“…The meta-analysis by Zhu et al [ 21 ] presented consistent results, reporting the beneficial effects of telemedicine strategies on all-cause hospitalisation, cardiac hospitalisation, all-cause mortality, and cardiac mortality. The positive effect of telemonitoring was also confirmed by Hafkamp et al [ 22 ], who found a lower risk of HF-related hospitalisations (HR = 0.86, 95% CI: 0.81–0.92, p < 0.001). Drews et al [ 5 ] summarised only studies in patients with HF decompensation within the previous month with intervention based on using telemonitoring, defined as the regular transmission of at least one physical variable at least once weekly.…”
Section: Telecare and Remote Disease Managementsupporting
confidence: 65%
“…[ 13 ] Further, interventions attempting to attenuate readmission have been studied, including the use of community health workers [ 14 , 15 ] and disease-specific interventions. [ 16 ] However, patient experience factors remain under-appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…It is the major cause of hospitalization in older people. Hospitalization due to HF increases healthcare resource utilization, as it accounts for more than half of total healthcare costs (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the specific cause of HF is crucial, due to the fact situations that reason HF might also require disorder specific treatment plans. The major goals of treatment in heart failure are (1) to improve prognosis and decrease mortality and (2)…”
Section: Introductionmentioning
confidence: 99%